(untitled) (Global Journal of Human-Social Science, 2013)
The intended end of this study is to trace the connection between language and ideology and how these connections are advocated in the evaluation of spoken texts in keeping with the Socio Cognitive Model 2002 of Van Dijk This study is also intended to explain that the political talk shows telecast byvarious private TV channels are apparent and conducive devices of ideology and concealed contexts and meanings which are not always vivid for readers and the viewers The researchers attempted to explore how the ideologies are portrayed in these shows through the analysis of a programme of a very popular talk show of a private television channel of Pakistan It also suggests that these talk shows bewilder the agency of systems by using various tactics In other words critical text analyses reveal how these selections lead debaters to manipulate the relations of agency and power in the representation of action to create specific connotations which are not always vivid for all readers and the viewers